Hot-dip galvanized aluminum magnesium steel with tensile strength larger than or equal to 1200 MPa and production method
By optimizing chemical composition and production process, hot-dip galvanized aluminum-magnesium steel plate with tensile strength and yield strength higher than 1150MPa was prepared, which solved the problem of insufficient tensile strength in the existing technology, and achieved ultra-high strength and corrosion resistance of the material The performance meets the high-strength and high corrosion resistance requirements in the fields of photovoltaic brackets, agricultural construction, logistics and transportation.
Patent Information
- Application Number
- CN202411371351.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
The tensile strength of the existing hot-dip galvanized aluminum-magnesium steel plates is insufficient, which cannot meet the high-strength and high corrosion resistance requirements in the fields of photovoltaic brackets, agricultural construction, logistics and transportation, and the corrosion resistance performance is not enough to meet the requirements of more than 25 years of use.
By optimizing chemical composition and production process, hot-dip galvanized aluminum-magnesium steel plates with tensile strength ≥1200MPa, yield strength ≥1150MPa and elongation ≥6%. The chemical compositions include C 0.26~0.32%, Si ≤0.5%, Mn 1.0~ 2.0%, P ≤0.02%, S ≤0.005%, Al 0.01~0.10%, N ≤0.01%, Cr 0.15~0.80%, B ≤0.001%, Nb or Ti ≤0.026%, V 0.05~0.20%, and adopt Conventional smelting, hot rolling, austenitization, rapid cooling and hot-dip galvanized aluminum-magnesium magnesium.
The ultra-high strength and corrosion resistance of the material have been achieved, and the corrosion resistance has reached more than 25 years, meeting the high strength and high corrosion resistance requirements in the fields of photovoltaic energy storage, agricultural construction and automobile transportation, and reducing the material usage and transportation costs. .
Smart Images

Figure CN119287270A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to ultra-high strength steel for photovoltaic energy storage, agricultural construction, automobile transportation and the like and a production method thereof, specifically, to hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200MPa and a production method thereof. Background Art
[0002] Environmental pollution and climate change are global problems facing mankind. To this end, countries around the world have signed a global agreement to reduce greenhouse gas emissions. Steel is the basic material for modern production and manufacturing, and is also the industry with the largest carbon emissions in the existing manufacturing industry. How to lead the green development of the steel industry through the collaboration of upstream and downstream industries has important social value. Optimize and improve the strength and application performance of steel materials, achieve lightweight components, and effectively reduce the use of steel materials.
[0003] At present, my country's photovoltaic brackets, agricultural buildings, logistics and transportation are widely used in hot-dip galvanized steel plates. The tensile strength of the material is generally only 235-335MPa, and there are problems such as thick material, heavy weight, high transportation cost, and inconvenient installation. At the same time, the corrosion resistance of the material is only about 8-10 years, which cannot meet the corrosion resistance requirements of photovoltaic power station users for more than 25 years. The newly emerged zinc-aluminum-magnesium coated steel plate has membrane self-repairing properties and good corrosion resistance. Its corrosion resistance is more than 3 times that of traditional hot-dip galvanized steel plates and can adapt to various harsh environments.
[0004] In order to improve the corrosion resistance of coated steel sheets, Japan, the United States and Europe took the lead in developing the addition of alloy elements such as Al, Mg, Ni, and Cr to hot-dip galvanized steel sheets, and developed three types of products: low-aluminum, medium-aluminum and high-aluminum series according to the different Al content of the surface coating. The alloy coating of hot-dip galvanized aluminum-magnesium steel sheets is formed by high-temperature solidification of zinc (Zn), aluminum (Al) and magnesium (Mg), and its microstructure is composed of a dense ternary eutectic structure of Zn, Al and MgZn2, so that a dense barrier is formed on the surface of the steel sheet that effectively prevents corrosion factors from penetrating, giving it good corrosion resistance (corrosion resistance is more than 3 times that of galvanized products of the same thickness), which can adapt to various harsh environments.
[0005] In recent years, domestic Baosteel, Jiugang, Shougang and other companies have developed and put into use aluminum-magnesium coated steel plate products, such as the following:
[0006] The document with Chinese patent publication number CN 110777290B discloses "A hot-dip galvanized aluminum-magnesium high-strength steel with a yield strength greater than 550MPa based on the CSP process". The chemical composition and weight percentage of its substrate are: C 0.055~0.10%, Si≦0.5%, Mn 0.55~1.7%, P≤0.0150%, S≤0.030%, Als: 0.015~0.045%, Ti+Nb≦0.1%, and the remainder is iron and unavoidable impurities.
[0007] The document with Chinese patent publication number CN 115109999 A discloses "A hot-dip galvanized aluminum-magnesium high-strength steel and its manufacturing method", the chemical composition and weight percentage of the base material are: C 0.18-0.22%, Si 0.2-0.3%, Mn0.5-1.0%, Als 0.02-0.05%, P≤0.02%, S≤0.008%, N≤0.008%, and the balance is Fe and unavoidable impurities; a thin-gauge galvanized aluminum-magnesium high-strength steel plate with a yield strength of more than 400MPa, a tensile strength of more than 500MPa and an elongation of more than 10% was successfully produced.
[0008] The document with Chinese patent publication number CN 113249648A discloses "An 800MPa grade hot-base zinc-aluminum-magnesium coated complex phase steel and its preparation method", the chemical composition and weight percentage of its substrate are: C 0.18-0.22%, Si 0.2-0.3%, Mn 0.5-1.0%, Als 0.02-0.05%, P≤0.02%, S≤0.008%, N≤0.008%, and the balance is Fe and unavoidable impurities.
[0009] The document with Chinese patent publication number CN 115198173A discloses "A 980MPa grade hot-dip galvanized complex phase steel, its steel matrix and preparation method", the chemical composition and weight percentage of the substrate are: C 0.08%~0.16%, Si 0.05%~0.1%, Mn 1.8%~2.5%, Al 0.02%~0.06%, P 0~0.008%, S 0~0.001%, Cr 0.05%~0.2%, Mo 0.2%~0.6%, V 0.001%~0.08%, Ti 0.02%~0.12%, and the rest are Fe and unavoidable impurities.
[0010] At present, the hot-dip galvanized aluminum-magnesium steel developed at home and abroad has a maximum tensile strength of only 980MPa, and there has been no report on the development and application of zinc-aluminum-magnesium coated steel plate materials above 1000MPa. Improving the strength of the material can meet the bearing capacity requirements of the steel structure while reducing the amount of material used, thereby achieving the essential carbon reduction of the steel structure, which is of great significance. Based on this, in order to better meet the green, low-carbon, and lightweight development and application needs in the fields of photovoltaic brackets, agricultural buildings, logistics and transportation, how to develop an ultra-high strength and high corrosion-resistant steel plate has become the research and development focus of the present invention. Summary of the invention
[0011] The present invention aims to overcome the problem that the zinc-aluminum-magnesium coated steel used for profile processing in the prior art generally has a material strength lower than that of the
[0012] In order to overcome the deficiency of ≤1000MPa, a hot-dip galvanized aluminum-magnesium steel and a production method thereof are provided, which have a yield strength ≥1150MPa, a tensile strength ≥1200MPa, an elongation ≥6%, and a corrosion resistance of more than 25 years.
[0013] Measures to achieve the above objectives:
[0014] A hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200MPa, wherein the components and weight percentage contents are: C: 0.26-0.32%, Si: not more than 0.5%, Mn: 1.0-2.0%, P≤0.02%, S≤0.005%, Als: 0.01-0.10%, N≤0.01%, Cr: 0.15-0.80%, B: not more than 0.001%, Nb≤0.026% or Ti≤0.026%, V: 0.05-0.20%, and the rest are Fe and unavoidable impurities; the microstructure is calculated by area ratio: the proportion of tempered troostite is not less than 90%, and the rest is tempered martensite.
[0015] Preferably, the weight percentage of Si is 0.35-0.46%.
[0016] Preferably, the weight percentage of Mn is 1.43-1.97%.
[0017] Preferably, the weight percentage of Als is 0.023-0.092%.
[0018] Preferably, the weight percentage of Cr is 0.18-0.76%.
[0019] Preferably, the weight percentage of Nb or Ti is 0.01-0.02%.
[0020] A method for producing a hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200MPa, comprising the following steps:
[0021] 1) Casting into billets after conventional smelting and conventional refining;
[0022] 2) heating the ingot and controlling the furnace temperature to be between 1150 and 1250°C;
[0023] 3) Hot rolling to product thickness, controlling the final rolling temperature to be no less than 880°C;
[0024] 4) Coil and air cool to room temperature;
[0025] 5) Perform austenitization, and control the austenitization temperature at 890-960°C;
[0026] 6) Rapidly cool the mixture to room temperature at a cooling rate of not less than 40°C / s;
[0027] 7) Remove the oxide layer on the surface of the steel, use pickling or EPS acid-free pickling or grinding to remove the oxide layer on the surface of the material;
[0028] 8) heating the steel after the oxide layer is removed, and the heating temperature is controlled at 350-480° C.;
[0029] 9) Hot-dip galvanizing aluminum and magnesium, control the temperature of the zinc pot at 420-480°C; the composition of the plating solution: Al: 1-10wt%, Mg:
[0030] 1~5%, the rest is Zn;
[0031] 10) After the coating thickness is controlled by the air knife, it is cooled to no more than 230°C by air cooling;
[0032] 11) Coiling or processing into shape.
[0033] Preferably, the steel heating temperature is between 409 and 475°C.
[0034] Preferably, the temperature of the zinc pot is between 430 and 475°C.
[0035] Functions and mechanisms of various raw materials and main processes in the present invention
[0036] C: Carbon is a basic element in steel and is also the most economical and effective strengthening element. If the carbon content is designed to be low, the material strength will decrease significantly; but if the carbon content is too high, the plasticity of the steel will be reduced and it will be detrimental to weldability. Therefore, considering the economy and comprehensive performance, the carbon percentage content in the present invention is controlled within the range of C 0.26-0.32%.
[0037] Si: Silicon is a solid solution strengthening element. It is dissolved in ferrite and is beneficial to the strength of the material. At the same time, silicon can inhibit the precipitation of cementite within a certain temperature range. With the increase of silicon content, the strength of steel increases significantly, the plasticity decreases significantly, and the welding performance decreases. Therefore, the content of Si in steel is usually controlled within 0.5%.
[0038] Mn: Manganese has a solid solution strengthening effect and is also one of the most important elements in the steel of the present invention. As is known to all, Mn is an important element for expanding the austenite phase region, which can reduce the critical quenching speed of steel, stabilize austenite, refine grains, and delay the transformation of austenite to pearlite. In the present invention, in order to ensure the strength of the steel plate, the Mn content should generally be controlled at more than 1.0%. If the Mn content is too low, the supercooled austenite will be unstable during air cooling in the first stage of segmented cooling, and it is easy to transform into a pearlite-type structure such as troostite; at the same time, the Mn content should generally not exceed 2.0%, and Mn segregation is likely to occur during steelmaking, and hot cracking is likely to occur during continuous casting of slabs. Therefore, the Mn content in steel is generally controlled at 1.0-2.0%.
[0039] P: Phosphorus is a harmful element in steel, which can easily cause center segregation of the ingot. It is easy to segregate to the grain boundary during the subsequent hot rolling heating process, which significantly increases the brittleness of the steel. At the same time, based on cost considerations and without affecting the performance of the steel, its content is controlled below 0.02%.
[0040] S: Sulfur is a very harmful element. Sulfur in steel often exists in the form of manganese sulfide. This sulfide inclusion will deteriorate the toughness of the steel and cause anisotropy of performance. Therefore, the sulfur content in the steel needs to be controlled as low as possible. Based on manufacturing cost considerations, the sulfur content in steel is controlled below 0.01%.
[0041] Als: Aluminum is added for deoxidation. When the Als content is less than 0.01%, its effect cannot be exerted. On the other hand, since adding a large amount of aluminum easily forms alumina agglomerates, the aluminum content is controlled in the range of 0.01 to 0.10%.
[0042] N: Nitrogen can improve the strength of steel; however, nitrogen has a strong bonding force with niobium and titanium, and will form coarse particles of niobium nitride and titanium nitride in steel at high temperatures, which seriously damages the plasticity and toughness of steel; in addition, a higher nitrogen content will increase the content of microalloying elements required to stabilize nitrogen, thereby increasing costs. Therefore, in the present invention, nitrogen is controlled to be below 0.01%.
[0043] Cr: Chromium can significantly improve the strength, hardness and wear resistance of steel, but it will reduce plasticity and toughness. At the same time, when the Cr content exceeds 0.8%, the risk of cracking of the ingot during continuous casting production increases. In the present invention, the chromium content is controlled at 0.15-0.80%.
[0044] B: Boron is an element that strongly improves hardenability. It only needs to be added in a very small amount to have a significant effect. The hardenability can be increased exponentially, thereby saving other expensive metal elements. Adding a small amount of boron to steel can significantly improve the hardenability of steel. However, too high a boron content can easily lead to an increase in the strength of the hot-rolled plate material and increase the difficulty of cold rolling. Therefore, the boron content in the present invention is controlled within the range of 0.0010%.
[0045] Nb or Ti: Niobium or titanium is a strong C and N compound forming element. Adding a small amount of niobium or titanium to steel can form a certain amount of its composite carbonitride, thereby hindering the growth of austenite grains, refining austenite grains, obtaining ultra-high strength, and improving steel plasticity and toughness. However, when excessive niobium or titanium combines with C to form coarse carbonitrides, it reduces the hardness and strength of the material, so control Nb≤0.026% or Ti≤0.026%.
[0046] V: Vanadium can improve the hardenability of steel, dissolve in ferrite to strengthen it, form stable carbides, and refine grains. N can strengthen the effect of V; a greater strengthening effect can be achieved by combining V precipitation strengthening with grain refinement. At the same time, V can reduce the decline in mechanical properties during hot-dip galvanizing. Therefore, its content is controlled at 0.05-0.20%.
[0047] The present invention adds Nb or Ti, V to form Nb / Ti / V (C, N) of a certain size in the matrix structure. This phase plays a pinning role in the austenitizing heating stage, hinders the growth of austenite, and promotes the formation of a refined austenite phase; at the same time, V can improve the steel's resistance to high-temperature tempering softening, reduce the decline in mechanical properties during hot-dip galvanizing, aluminum-magnesium processing, and ensure that the material has good tensile strength.
[0048] The reason why the present invention controls the austenitizing temperature at 890-960°C is that it can make the steel plate have a good match of strength and toughness and improve the comprehensive performance of the steel plate. The product after hot rolling or cold rolling is heated and kept warm in the austenite zone to make the material completely austenitized; then it is quickly cooled to transform the austenite into martensite, thereby obtaining a higher material strength; then, after heating the steel, the zinc pot is heated to 420-480°C for hot-dip galvanizing aluminum and magnesium, so as to achieve high-temperature tempering of the material, obtain the troostite structure, and improve the yield strength and toughness of the material; when the temperature is lower than 890°C, it is easy to cause insufficient austenitization of the material, and if the temperature is higher than 960°C, it is easy to cause a significant increase in the austenite grain size, making the material strength lower than 1200MPa.
[0049] The reason why the present invention controls the cooling rate to be not less than 40°C / s is that when the cooling rate is too low, the austenite structure cannot be completely transformed into the martensite structure with higher strength, and the ultimate tensile strength performance of the material is never affected.
[0050] The present invention controls the steel material to be heated to 350-480°C first, and then controls the zinc pot temperature to be 420-480°C during hot-dip galvanizing of aluminum and magnesium. This is because if the steel material temperature is too low, the zinc pot temperature will be significantly reduced during galvanizing, and if the zinc pot temperature is too low, it will directly affect the fluidity of zinc liquid and the surface galvanizing quality; if the steel material temperature is too high, the zinc pot temperature will increase during galvanizing, and if the zinc pot temperature is higher than 480°C, zinc will be vaporized and volatilized, increasing production costs.
[0051] Compared with the prior art, the yield strength of the present invention is ≥1150MPa, the tensile strength is ≥1200MPa, and the elongation is ≥6%. After a neutral salt spray test, the corrosion resistance of the present invention is improved from less than 10 years of traditional galvanizing to more than 25 years. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is the metallographic structure diagram of the present invention. DETAILED DESCRIPTION
[0053] The present invention is described in detail below:
[0054] Table 1 is a list of chemical components of various embodiments and comparative examples of the present invention;
[0055] Table 2 is a list of main process parameters of various embodiments and comparative examples of the present invention;
[0056] Table 3 is a table of performance test results of various embodiments of the present invention and comparative examples.
[0057] Each embodiment of the present invention is produced according to the following steps
[0058] 1) Casting into billets after conventional smelting and conventional refining;
[0059] 2) heating the ingot and controlling the furnace temperature to be between 1150 and 1250°C;
[0060] 3) Hot rolling to product thickness, controlling the final rolling temperature to be no less than 880°C;
[0061] 4) Coil and air cool to room temperature;
[0062] 5) Perform austenitization, and control the austenitization temperature at 890-960°C;
[0063] 6) Rapidly cool the mixture to room temperature at a cooling rate of not less than 40°C / s;
[0064] 7) Remove the oxide layer on the surface of the steel, use pickling or EPS acid-free pickling or grinding to remove the oxide layer on the surface of the material;
[0065] 8) heating the steel after the oxide layer is removed, and the heating temperature is controlled at 350-480° C.;
[0066] 9) Hot-dip galvanizing aluminum and magnesium, control the temperature of the zinc pot at 420-480°C; the composition of the plating solution: Al: 1-10wt%, Mg:
[0067] 1~5%, the rest is Zn;
[0068] 10) After the coating thickness is controlled by the air knife, it is cooled to no more than 230°C by air cooling;
[0069] 11) Coiling or processing into shape.
[0070] Table 1 List of chemical composition values of various embodiments and comparative examples of the present invention (wt.%)
[0071]
[0072]
[0073] Table 2 List of main process parameter values of various embodiments of the present invention and comparative examples
[0074]
[0075] Table 3 Performance test results of various embodiments of the present invention and comparative examples
[0076]
[0077]
[0078] It can be seen from Table 3 that the strip steel for profiles produced by the alloy composition design and related processes of the present invention has good mechanical properties, yield strength ≥1150MPa, tensile strength ≥1200MPa, and elongation ≥6%; at the same time, due to the coordinated effect of Zn / Al / Mg in the coating, the material has more outstanding corrosion resistance than galvanized sheet, meeting the ultra-high strength and high corrosion resistance requirements for profiles such as photovoltaic energy storage, agricultural construction, and automobile transportation.
[0079] This specific implementation is only the best example and is not a restrictive implementation of the technical solution of the present invention.
Claims
1. A hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200MPa, wherein the components and weight percentages are: C: 0.26-0.32%, Si: not more than 0.5%, Mn: 1.0-2.0%, P≤0.02%, S≤0.005%, Als: 0.01-0.10%, N≤0.01%, Cr: 0.15-0.80%, B: not more than 0.001%, Nb≤0.026% or Ti≤0.026%, V: 0.05~0.20%, and the rest are Fe and inevitable impurities; the microstructure is calculated by area ratio: tempered troostite accounts for not less than 90%, and the rest is tempered martensite.
2. The hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200MPa according to claim 1, characterized in that: The weight percentage of Si is 0.35-0.46%.
3. The hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200MPa according to claim 1, characterized in that: The weight percentage of Mn is 1.43-1.97%.
4. The hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200MPa according to claim 1, characterized in that: The weight percentage of Als is between 0.023% and 0.092%.
5. The hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200MPa according to claim 1, characterized in that: The weight percentage of Cr is between 0.18% and 0.76%.
6. The hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200 MPa according to claim 1, characterized in that: The weight percentage content of Nb or Ti is 0.01-0.019%.
7. A method for producing a hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200 MPa as claimed in claim 1, comprising the following steps: 1) Casting into billets after conventional smelting and conventional refining; 2) heating the ingot and controlling the furnace temperature to be between 1150 and 1250°C; 3) Hot rolling to product thickness, controlling the final rolling temperature to be no less than 880°C; 4) Coil and air cool to room temperature; 5) Perform austenitization, and control the austenitization temperature at 890-960°C; 6) Rapidly cool the mixture to room temperature at a cooling rate of not less than 40°C / s; 7) Remove the oxide layer on the surface of the steel, use pickling or EPS acid-free pickling or grinding to remove the oxide layer on the surface of the material; 8) heating the steel after the oxide layer is removed, and the heating temperature is controlled at 350-480° C.; 9) Hot-dip galvanizing of aluminum and magnesium, controlling the temperature of the zinc pot at 420-480°C; the composition of the plating solution: Al: 1-10wt%, Mg: 1-5%, and the rest Zn; 10) After the coating thickness is controlled by the air knife, it is cooled to no more than 230°C by air cooling; 11) Coiling or processing into shape.
8. The method for producing hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200 MPa according to claim 7, characterized in that: The steel heating temperature is between 409 and 475°C.
9. The method for producing hot-dip galvanized aluminum-magnesium steel with a tensile strength of ≥1200 MPa according to claim 7, characterized in that: The zinc pot temperature is between 430 and 475°C.
Citation Information
Patent Citations
A hot-dip galvanized aluminum-magnesium high-strength steel, its preparation method and application
CN110777290B
800 MPa-grade hot-based zinc-aluminum-magnesium coating complex phase steel and preparation method thereof
CN113249648A
Hot-dip zinc-aluminum-magnesium-plated high-strength steel and manufacturing method thereof
CN115109999A
980MPa-grade hot-based galvanized complex-phase steel and steel matrix and preparation method thereof
CN115198173A